Existence and Concentration of Solutions for a Class of Elliptic Problems with Discontinuous Nonlinearity in R^N - Alves, Claudianor O.; Nascimento, Rúbia G. (MATHEMATICA SCANDINAVICA, 2013)
Using variational methods we establish existence and concentration of positive solutions for a class of elliptic problems in R^N, whose nonlinearity is discontinuous.